Challenges in the diagnosis of an unusual retroperitoneal pararenal well-differentiated Liposarcoma: A case report unraveling the complexities of genetic alterations and histomorphology (Indian Journal of Case Reports, 2025)
Liposarcomas (LPS) presents diagnostic challenges, particularly when located in pararenal retroperitoneal regions near vital organs such as the kidneys and adrenal glands. Herein, we report a novel case of well-differentiated liposarcoma (WDLPS) with myxoid features and murine double minute 2 (MDM2)-DNA damage-inducible transcript 3 (DDIT3) co-amplification in a 50-year-old male, presented with right-sided abdominal pain and a palpable mass in the lumbar and hypogastric regions. Imaging revealed a large retroperitoneal mass displacing the adjacent organs. Histological examination showed a poorly circumscribed hypocellular mass comprised of stellate spindle cells in abundant myxoid stroma. Focal areas of increased cellularity and frequent mitoses were noted. Overall histological and immunohistochemistry suggested diagnosis of myxoid liposarcoma, however, Fluorescence in situ hybridization (FISH) test showed no fusion of FUS-DDIT3 fusion, typically seen in myxoid liposarcoma. Occasional lipoblasts were seen. FISH test for MDM2 and DDIT3 showed co-amplification of both genes. The overlap between WDLPS, MLS, and Dedifferentiated LPS highlights the necessity of thorough histological and genetic analyses for accurate diagnosis and treatment planning. This case underscores the recognition of DDIT3 amplifications and its association with ML-like changes in LPS, which further can aid in resolving diagnostic challenges, particularly in cases with atypical morphological features.